Supreme Court expansion of presidential power : unconstitutional leaning - Fisher, Louis (University Press of Kansas, 2017)
"Fisher traces the development of the constitutional law of presidential power through federal judicial decisions. He argues that the federal courts since the 1930s have greatly expanded presidential power beyond any fair reading of the original intent of the Framers and the text of the Constitution. Fisher's conclusion is twofold : not only should the courts be held accountable for misleading approaches, biased doctrines, and abdication of function, but so should constitutional law scholars, who have not mined the historical record nor questioned presumptions about executive competence. The result is that both judges and the scholars who comment on their work have legitimized executive power to an extent that has done serious damage not only to the constitutional system, but also to the viability and legitimacy of public policy"--